NG2-Glia Transiently Overcome Their Homeostatic Network and Contribute to Wound Closure After Brain Injury - von Streitberg, Axel; Jäkel, Sarah; Eugenin von Bernhardi, Jaime; Straube, Christoph; Buggenthin, Felix; Marr, Carsten; Dimou, Leda (Frontiers in Cell and Developmental Biology, 2021)
In the adult brain, NG2-glia represent a cell population that responds to injury. To further investigate if, how and why NG2-glia are recruited to the injury site, we analyzed in detail the long-term reaction of NG2-glia after a lesion by time-lapse two-photon in vivo microscopy. Live imaging over several weeks of GFP-labeled NG2-glia in the stab wounded cerebral cortex revealed their fast and heterogeneous reaction, including proliferation, migration, polarization, hypertrophy, or a mixed response, while a small subset of cells remained unresponsive. At the peak of the reaction, 2–4 days after the injury, NG2-glia accumulated around and within the lesion core, overcoming the homeostatic control of their density, which normalized back to physiological conditions only 4 weeks after the insult. Genetic ablation of proliferating NG2-glia demonstrated that this accumulation contributed beneficially to wound closure. Thus, NG2-glia show a fast response to traumatic brain injury (TBI) and participate in tissue repair.